Case Report: Systemic Amyloidosis Involving the Heart and Skeletal Muscle - Lv, Pinchao; Li, Yuxi; Wu, Lin; Shi, Qiuping; Meng, Lingchao; Yu, Xiaojuan; Nong, Lin; Li, Jianping (Frontiers in Cardiovascular Medicine, 2022)
Amyloidosis refers to an etiologically heterogeneous proteins misfolding disease characterized by extracellular deposition in organs and tissues of amyloid fibers, leading to severe organ dysfunction and death. Systemic amyloidosis often involves multiple organs. Heart and kidney are the most commonly affected organs, while skeletal muscle involvement is rare and often accompanied by the other organs’ involvement. We reported a 70-year-old man manifested with myopathy followed by heart failure who was suspected of transthyretin amyloidosis clinically, after the pathological results and the PYP radionuclide scanning, light-chain(AL) amyloidosis involving the heart and skeletal muscle was confirmed. His unique presentation gives insight into a rare but debilitating disorder and the potential link between various types of amyloidosis.